Ticagrelor alleviates pyroptosis of myocardial ischemia reperfusion-induced acute lung injury in rats: a preliminary study - Dai, Yi-Ning; Wang, Li-Tao; Zhang, Ye-Shen; Xue, Ling; He, Peng-Cheng; Tan, Ning; Liu, Yuan-Hui (PeerJ (San Francisco, CA), 2024)
Pulmonary infection is highly prevalent in patients with acute myocardial infarction undergoing percutaneous coronary intervention. However, the potential mechanism is not well characterized. Myocardial ischemia-reperfusion injury (MIRI) induces acute lung injury (ALI) related to pulmonary infection and inflammation. Recent studies have shown that pyroptosis mediates ALI in several human respiratory diseases. It is not known whether MIRI induces pyroptosis in the lungs. Furthermore, ticagrelor is a clinically approved anti-platelet drug that reduces ALI and inhibits the expression levels of several pyroptosis-associated proteins, but the effects of ticagrelor on MIRI-induced ALI have not been reported. Therefore, we investigated whether ticagrelor alleviated ALI in the rat MIRI model, and its effects on pyroptosis in the lungs. Sprague-Dawley rats were randomly divided into four groups: control, MIRI, MIRI plus low ticagrelor (30 mg/kg), and MIRI plus high ticagrelor (100 mg/kg). Hematoxylin and Eosin (HE) staining was performed on the lung sections, and the HE scores were calculated to determine the extent of lung pathology. The wet-to-dry ratio of the lung tissues were also determined. The expression levels of pyroptosis-related proteins such as NLRP3, ASC, and Cleaved caspase-1 were estimated in the lung tissues using the western blot. ELISA was used to estimate the IL-1β levels in the lungs. Immunohistochemistry was performed to determine the levels of MPO-positive neutrophils as well as the total NLRP3-positive and Cleaved caspase-1-positive areas in the lung tissues. The lung tissues from the MIRI group rats showed significantly higher HE score, wet-to-dry ratio, and the MPO-positive area compared to the control group, but these effects were attenuated by pre-treatment with ticagrelor. Furthermore, lung tissues of the MIRI group rats showed significantly higher expression levels of pyroptosis-associated proteins, including NLRP3 (2.1-fold, P < 0.05), ASC (3.0-fold, P < 0.01), and Cleaved caspase-1 (9.0-fold, P < 0.01). Pre-treatment with the high-dose of ticagrelor suppressed MIRI-induced upregulation of NLRP3 (0.46-fold, P < 0.05), ASC (0.64-fold, P < 0.01), and Cleaved caspase-1 (0.80-fold, P < 0.01). Immunohistochemistry results also confirmed that pre-treatment with ticagrelor suppressed MIRI-induced upregulation of pyroptosis in the lungs. In summary, our data demonstrated that MIRI induced ALI and upregulated pyroptosis in the rat lung tissues. Pre-treatment with ticagrelor attenuated these effects.